1986
DOI: 10.1071/ar9860157
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the total and component galactosyl sucrose oligosaccharides of Lupinus species

Abstract: The oligosaccharide compositions of 33 lupin seed accessions and cultivars, from 10 species, are reported. Seed weights varied from 3.8 to 66.6 g/100 seeds. Total oligosaccharide content ranged from just under lo%, to almost 23% dry matter. In all cases the quantity of oligosaccharides (raffinose, stachyose and verbascose) was higher than that of disacharides (sucrose and melibiose). Verbascose ranged from 0.0 to 33.4% of total oligosaccharide content, and raffinose from 4.7 to 47.4%. Stachyose was the predomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 6 publications
1
21
0
Order By: Relevance
“…Starch content was determined in chickpea, experimental diets and ileal digesta by an enzymatic method (Longstaff and McNab, 1991). Tannins, phytate, a -galactosides and sapogenol-b contents were analysed in chickpeas following the methods of Swain and Hillis (1959), Burbano et al (1995), Saini and Gladstones (1986) and Muzquiz et al (1993) respectively. For amino acid analysis, chickpea samples were hydrolysed according to the method of Jones et al (1981).…”
Section: Chemical Analysismentioning
confidence: 99%
“…Starch content was determined in chickpea, experimental diets and ileal digesta by an enzymatic method (Longstaff and McNab, 1991). Tannins, phytate, a -galactosides and sapogenol-b contents were analysed in chickpeas following the methods of Swain and Hillis (1959), Burbano et al (1995), Saini and Gladstones (1986) and Muzquiz et al (1993) respectively. For amino acid analysis, chickpea samples were hydrolysed according to the method of Jones et al (1981).…”
Section: Chemical Analysismentioning
confidence: 99%
“…The author found that treatment of meal with 60% methanol/water solution (60) resulted in incomplete extraction of the a-galactosides. On the other hand, extraction of plant material in boiling aqueous ethanol (63) or in aqueous ethanol at 65 °C (64) or in water at 30 °C (65) afforded comparable results for some seeds. Muzquiz et al (66) evaluated two procedures for extraction of a-galactosides from lupin species.…”
Section: Quantification Of Oligosaccharidesmentioning
confidence: 84%
“…The aforementioned oligosaccharides are not digested by the monogastric animals, and are therefore available for bacterial fermentation to produce short-chain fatty acids and gas (Guillon and Champ 2002). High levels of oligosaccharides, in particular α-galactosides, can by certain means be even considered as antinutritional factors, as their fermentation in monogastric animals can lead to the increased fluid retention, hydrogen production, and can impair the utilization of nutrients (Saini and Gladstones 1986). Therefore, the particular source and concentration of these compounds should always be tested in vivo.…”
Section: Discussionmentioning
confidence: 99%